KUTILAS (KURIKULUM 2013) DAN PROFESI GURU SEKOLAH DASAR - Reky Lidyawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2013)
The dynamics of the development of the current curriculum has a significant influence on the implementation of learning in elementary school, the separate subject curricullum into integrated curricullum. With the changes in this curriculum requires elementary teachers to be more professional in teaching, as must be able to draw on some lessons into one theme. Teachers are professional educators who have competence education to the primary task of educating, teaching, guiding, directing, train, assess, and evaluate students on early childhood education, formal education, primary education, and secondary education. With the current curriculum development dynamics proper to the professional teacher education equip themselves with adequate competence